Verifying on-line handwritten signature using neural networks approach - Siraj, Fadzilah; Zakaria, Azizi; Wan Ishak, Wan Hussain (Pusat Penyelidikan dan Perundingan, Universiti Utara Malaysia, 2000)
Signatures are used everyday to authorize the transfer of funds for bank cheques, credit cards, legal documents and others. Forgeries on banking and business transactions amount to a large sum of money every year. Although the cashier sometimes can spot the forgeries, it is not cost effective to check the forgeries manually. Hence, automated verification is available, this will certainly benefit the customers and promote Electronic Commerce. Thus handwritten signature verification system can play an important role in future reading system (Bartneck, 1996).It is a worthy and challenging area of further investigation (Cote et, al, 1998). This paper discusses the neural network models and thus identifies suitable model for on-line Handwritten Signature Verification. Such a model is implemented and the performance of the neural network model is evaluated.